Which complexity characteristics do economical industries present? - Aita Ramírez Gastón, Rafael Martín Antonio (2020)
The past decade has seen a development of complex theories in different fields, raising the question: should managers use complex principles in their strategy? The answer implies to analyze companies and economical industries where they develop as a complex system. This paper study seven characteristics that define complex systems and analyzes if they can be observed in economical industries.